Technological Innovation accelerating Industry 4.0 Impact on Retail Sector– A Exploratory Study on SPAR - Mallik, D M Arvind; Patel. S, Arpitha (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the research report is to advance the understanding of degree of knowledge, the perceived relevance and the current practice of Industry 4.0 in spar retail environment. The main objectives are to study the Managerial implications of technological innovation in the path towards Industry 4.0 in Retail. The present study is conducted for six weeks. Sample size is100 and followed by explanatory research design and a convenient sampling was used. Digitization of product and service offerings; developing innovative digital business models; digitization and integration of supply chains; and adopting data and analytics as a core capability will lead higher driving forces to industry4.0. The results are of importance for retail companies in planning transformation processes towards digitalized processes and enhance employee awareness towards Industry 4.0 must be initiated from Management and HR Dept will have key role to perform